TINGGALAN TRADISI MEGALITIK DI DESA BASANGALAS, KECAMATAN ABANG, KABUPATEN KARANGASEM - Yogi Prabhawa, Kadek (Humanis; Volume 7. No. 3. Juni 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Archeology studies try to reconstruct human culture in the past and to overview the process of culture change in the past through objects left behind. Relics in the past basically contain a very high historical value. Elements of culture in the past in this study concerning finding of the elements of megalithic tradition at Kayu Sakti Temple, Ponjok Batu Temple, Dalem Basangalas Temple, the findings were a throne of rock, stone mortars, monoliths, and the structure of natural stone, that exist in the Basangalas village. Subdistrict of Abang, Karangasem regency The author of this study are interested to study the relic of the megalithic tradition in the Basangalas village because there are still a number of unresolved aspects. The problem has been formulated that are to know the shape, function, and meaning of the relic of megalithic tradition in the Basangalas village. The result of the analysis of relic form of megalithic tradition in the Basangalas village shows there are variations of local form in the form of combination with bebaturan shape and it has been development very long and it still growing at this time. Analysis of the function of relic of megalithic tradition in the Basangalas village shows that the relic of the megalithic tradition is still sacred by the public and it used as a medium of religious worship in the life of the local community. The relic of megalithic tradition in the Basangalas village has symbolic significance as a religious ceremony and worship. Tradition of megalithic in the Basangalas village is a megalithic tradition that is still alive. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: relic of megalithic tradition, form, function and meaning